Pengaruh Direct Intruction Model Terhadap Peningkatan Kemampuan Teknik Dasar Permainan Bola Voli Siswa Menengah Atas - Divaldo Taneo; Ega Trisna Rahayu; Citra Resita; Rina Marlina; Evi Susianti (Peneliti.net, 2022)
This research aims to find out 1) the difference in the effect of the Direct Intruction Model on the passing down 2) the difference between before and after model. 3) to know the difference the method used in this research is. Fixed and Rotational Paired Down passing is a from of basic bottom passing ability training. The Problems raised in this study are 1) There are student and students who cannot do passing down 2) Lack Understanding Passing Down 3)Practice Value volley ball I see low. experimental 11 MIPA 2 target passing down from students 11MIPA2 totaling 20 people. The sampel of this research is half of the mathematics and natural sciences class, which is 20 people and the number is 45 people. The results showed that the correlatiaon (0,743) and the contingent coefficient (0.003) of the two research methods, it shows that there is a better change in students with lowr passing through the Direct Intruction Model. The conclusions of this research are 1) there is pendanub lower passing practice with Direct Intruction Model